Identidades, territorios y conflictos: Hacia una antropología contextual e histórica en el Cauca, sur de Colombia - Álvaro René Garcés-Hidalgo (Jangwa Pana, 2016)
This article combines some elements of theoretical type taken from anthropological perspectives trying to facilitate understanding of a specific event to analyze the phenomenon of conflict, identities and territories in south western Colombia, specifically in the department of Cauca, one of places of greater political, social and cultural tension in the country. This text also exposes of anthropological considerations, several aspects that could serve as methodological and epistemological routes to address such situations. In the text reflection points are developed from anthropological categories as otherness and identity, trying, from these, generates an interpretive framework of the context of this part of Colombia. One of the objectives of this work is to try to correct the problems in terms of research are presented for the case of this region, because although treated from different, very little has been done from anthropology to respect.In short it is a kind of landing theory to a case study that aims to show how they operate phenomena such as colonialism and other speeches in a sphere of microanalysis.